Prevalensi dan Intensitas Ektoparasit Ika Nila (Oreochromis niloticus) di Bendungan Telaga Tunjung, Tabanan - Ida Ayu Grisandi Dewi Kurnia; Pande Gde Sasmita Julyantoro; Endang Wulandari Suryaningtyas (Current Trends in Aquatic Science, 2019)
This study aims to determine the value of the prevalence and intensity of ectoparasites in Tilapia (Oreochromis niloticus) in Telaga Tunjung Dam and measure the parameters of water quality, temperature, pH, and DO. The number of tilapia studied was 30, sampling was done at 3 stations in Telaga Tunjung Dam. Identification of ectoparasites was carried out at the Fisheries Science Laboratory, Water Resources Management Study Program, Faculty of Marine and Fisheries, Udayana University. Ectoparasites were identified in the mucus, dorsal, caudal, operculum and gill organs of the tilapia by skin scraping and wet mount methods. Data were analyzed by descriptive quantitative which calculated differences in the prevalence and intensity of ectoprasite infections and correlation tests to determine the relationship of length and weight of fish with intensity. The results of the three stations show the prevalence value with the "Usually" criteria, which is still in the level of "Medium" infection. At stations I and III the prevalence value is 70% and at station II is 80%. The intensity value obtained at station I is 6.7 (tail / ind) the level of infection is "Medium", whereas in stations II and III the infection rates are "Low" which are 3.5 and 4.0 (tail / ind). After a correlation test, it was found that the relationship between the length and weight of tilapia with ectoparasite intensity was positively correlated with values ??of 0.1876 and 0.0878. The results of temperature water quality parameters in the three stations ranged from 26.8 -28.2 ?, for the results of pH values ??in the three stations ranged from 7.3 to 8.2 and the results of DO parameter values ??ranged from 4.3 to 5.5 mg / l, where the results of measurements of temperature, pH and DO water quality parameters in the Telaga Tunjung Dam are still in the optimal category.